2011
DOI: 10.4236/health.2011.35045
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the relationship between body mass index (BMI) and dental age

Abstract: The aim of the study was to determine the rela-tionship between Body Mass Index (BMI) and accelerated dental development. The dental developmental ages of 100 children aged between 8 and 12 years were determined using the Demirjian method and panoramic radiographs. BMI status was determined for each subject on the basis of the system developed by the International Obesity Task Force. There was a significant direct relationship between dental development and BMI (P < 0.01). Obese children have a higher rate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 14 publications
3
20
1
Order By: Relevance
“…In both males and females, lower BMI is associated with a delay in the age of attainment of the final H dental developmental stage. This is in agreement with previous studies that found a significant influence of nutrition on tooth formation in children from the United States (Hilgers et al, ; Mack et al, ) and Iran (Zangouei‐Booshehri et al, ). The findings of the present study are at variance with three previous reports of no significant difference in the dental development of underweight or overweight children (Bagherian & Sadeghi, ; Eid et al, ; Elamin & Liversidge, ).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In both males and females, lower BMI is associated with a delay in the age of attainment of the final H dental developmental stage. This is in agreement with previous studies that found a significant influence of nutrition on tooth formation in children from the United States (Hilgers et al, ; Mack et al, ) and Iran (Zangouei‐Booshehri et al, ). The findings of the present study are at variance with three previous reports of no significant difference in the dental development of underweight or overweight children (Bagherian & Sadeghi, ; Eid et al, ; Elamin & Liversidge, ).…”
Section: Discussionsupporting
confidence: 93%
“…Studies from Peru, Brazil, Iran, and Northern Sudan that used BMI as a proxy for nutritional status found no significant influence of BMI on tooth formation (Bagherian & Sadeghi, ; Cameriere et al, ; Eid et al, ; Elamin & Liversidge, ). In contrast, other studies (DuPlessis, Araujo, Behrents, & Kim, ; Hilgers et al, ; Mack, Phillips, Jain, & Koroluk, ; Zangouei‐Booshehri, Ezoddini‐Ardakani, Aghili, & Sharifi, ) showed dental development was significantly accelerated with higher BMI, even after adjusting for age and sex. This developmental advancement was attributed to accelerated linear growth and early sexual maturation, which is usually associated with obesity (Sánchez‐Pérez, Irigoyen, & Zepeda, ; Slyper, ).…”
Section: Introductionmentioning
confidence: 79%
“…[23][24][25][26] Underweight children showed retarded eruption of teeth, this is consistent with a study done in India by Manjunatha (2014) and in Germany by Heinrich-Weltzien et al (2013), who reported that underprivileged children show comparative retarded eruption relative to their ethnic counterparts from higher socioeconomic status. 27,28 In our study, major differences of eruption times of teeth were present among children with the same chronological age which is consistent with a study done in Iran by Booshehri et al (2011), who also concurred that same finding. Table 5 Eruption of Mandibular teeth in relation to age Table 4 Eruption of Maxillary teeth in relation to age.…”
Section: Discussionsupporting
confidence: 82%
“…4,5 As teeth are the most stable structures in the human body, it can be of paramount importance in forensic medicine where estimation of age is usually required for criminal investigations and also in persons who do not have proper birth certificates whether above or below 18 years of age. 6,7 Body Mass Index (BMI) is a reliable table for measurement of obese people and for those who are overweight especially teenagers and small kids. BMI is reliant on age and gender in kids and teenagers and is for the most part stated to as particular for a specific age 8 but, no sound research has been performed in Pakistan on the assessment of eruption of permanent teeth according to age and its relation with body mass index.…”
Section: Introductionmentioning
confidence: 99%
“…Heavier children showed a slight advancement in tooth formation across all ages evidenced by negative correlation of age of tooth stage and body fat [2]. Accelerated dental maturity was observed in obese or overweight children compared to normal and underweight children [22], [23] but subgroups consisted of only15 or 16 over a wide age range. Accelerated dental maturity was reported in 23 overweight and 18 obese children aged 8 to 15 [24].…”
Section: Introductionmentioning
confidence: 99%